Morality behind Prohibition of Abortion and The Meaning of Medical Emergency As a Legal Basis for Abortion - Arif, Fahmi (Martabat: Jurnal Perempuan dan Anak, 2024)
Morality behind prohibition of abortion remains one of the most controversial issues in modern society. Proponents of abortion rights emphasize the importance of women's rights to their own bodies and the freedom for women to make decisions regarding reproductive rights. Opponents of abortion argue that the life of the fetus must be protected even during pregnancy. The party in the middle position in this debate tries to balance these two interests, namely a woman's autonomy over her body and the right to life of the fetus, so that a legal instrument is needed to limit the cases in which abortion can be legally carried out. This research aims to uncover questions about the morality of abortion in the Indonesian legal system and the meaning of medical emergencies as a basis for the legality of abortion. Abortion in Indonesia's legal system emphasizes the right to life of the fetus as a potential baby and does not fully consider social dynamics and women's autonomy over their bodies and reproduction. Medical emergencies are regulated in the 2014 Government regulations, where new implementing regulations should be issued to accommodate the provisions of the New Criminal Code and the Health Law as well as developing social dynamics.